O efeito moderador da cocriação de valor na relação entre motivação de aprendizagem autodeterminada e motivação para empreender : um estudo em ambientes educacionais de ensino superior - Melo, Bruna Silva de (2022)
The value co-creation has been seeking answers in scientific studies to reinforce the importance of the service focused on customer's skills and knowledge, generating joint value creation. In academic environments, for instance, the co-creation has been addressed from different perspectives; all things considered, the desire is to show that, when academics actively participate in the learning process, the co-creation happens. Studies on the field of learning motivations explain the motives that conduct academics for effective learning. The self-determination theory describes the extrinsic and intrinsic motivations of academics, demonstrating how the continuum of mostly autonomous learning interferes with their motivations. It further explains that extrinsic motivations generate less autonomy for academics in the learning process and intrinsic motivations generate greater autonomy. These motivations have been studied from the perspective of influence on entrepreneurial motivation, but the results that have been obtained do not contribute to the intentions of institutions of fomenting entrepreneurship. Although academic environments are aimed toward the development of entrepreneurship, academics refute this possibility and, when they endeavor on entrepreneurship, they do so for motives outside the university. In the quest to fill the gap between these motivations, and using a quantitative method, a survey was applied to 426 academics from a business school in Porto Alegre (RS). The goal was to evaluate the effect of co-creation on the relationship between extrinsic and intrinsic motivations and on entrepreneurial motivation. The results indicate good relationships among the constructs and a good explanatory capacity of the model. The moderation showed results not yet found in the literature, especially regarding the relationship between intrinsic motivations on entrepreneurial motivation. With these results, gaps were filled, which contribute to the Marketing area and the applicability in the teaching environments of business schools that aim the development of entrepreneurship.